Organizational silence in government banks, and its relationship to the Counterproductive work behavior - Hadi Neamah, Asmaa (Iraqi Journal for Administrative Sciences, 2024)
The aim of the research is to know the most important factors causing organizational silence for employees and to know the extent to which this is reflected in the performance of their tasks and behavior, as well as knowing the behavior of employees that violate organizational rules and procedures that harm the organization’s work and performance. Therefore, the research sought to verify the extent to which workers were exposed to organizational silence, and then to stand on the repercussions of that and its reflection in work behavior in reverse. Therefore, the choice was made on a random sample of 53 employees of the branches of government banks in Karbala governorate (Al-Rasheed Bank, Al-Rafidain Bank, Agricultural Bank, Real Estate Bank) by distributing the questionnaire form. The bank employees in the research sample avoid disclosing any information that is harmful to their co-workers, as well as employees hiding information that may cause them problems with the organization's officials, which means that the biggest reason for the occurrence of organizational silence is a social reason.